2012
DOI: 10.1158/0008-5472.can-11-3951
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Protein Nodal Promotes Breast Cancer Vascularization

Abstract: Tumor vascularization is requisite for breast cancer progression, and high microvascular density in tumors is a poor prognostic indicator. Patients bearing breast cancers expressing human embryonic stem cell (hESC)-associated genes similarly exhibit high mortality rates, and the expression of embryonic proteins is associated with tumor progression. Here, we show that Nodal, a hESC-associated protein, promotes breast cancer vascularization. We show that high levels of Nodal are positively correlated with high v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 44 publications
(56 reference statements)
5
44
0
Order By: Relevance
“…It also highlights the potential for targeting Nodal in breast cancer. Adding to this information, another study examined vascularization in breast cancer samples and found that levels of Nodal protein within tumors correlated with microvascular density as assessed by CD31 staining [161]. In vitro analysis in this study revealed that Nodal regulated factors associated with angiogenesis such as VEGF and PDGF in breast cancer cells.…”
Section: Nodal and Cancermentioning
confidence: 86%
“…It also highlights the potential for targeting Nodal in breast cancer. Adding to this information, another study examined vascularization in breast cancer samples and found that levels of Nodal protein within tumors correlated with microvascular density as assessed by CD31 staining [161]. In vitro analysis in this study revealed that Nodal regulated factors associated with angiogenesis such as VEGF and PDGF in breast cancer cells.…”
Section: Nodal and Cancermentioning
confidence: 86%
“…[21][22][23] Studies have correlated the altered expression of Nodal with the development, progression, and aggressiveness of various cancers. 7,[24][25][26] We have previously observed reduced Cripto messenger RNA (mRNA) levels in endometriotic lesions as well as in the eutopic endometrium of affected women. 3,27 However, no previous study has evaluated the protein levels of Nodal and Cripto and the SMADs involved in their signaling pathway in women with endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that higher levels of Nodal are found within TNBC even when compared to invasive receptor positive tumors (summarized in Table 1), and are in agreement with studies that have reported correlations with Nodal expression and aggressive cancer-related characteristics. 13,15,[18][19][20][21][22][23] Collectively, our results demonstrate the robust presence of Nodal in TNBC samples, representing a potential new target for this disease.…”
Section: Resultsmentioning
confidence: 76%